Toward an Understanding of the Metropolis - Haig, Robert Murray (Quarterly Journal of Economics, 1926)
Where do things "belong" in an urban area? 404. — Inadequacy of current analysis, 404. — Study of location trends in New York as a method of attacking the problem, 406. — Summary of trends in location of manufacturing and other economic activities, 407. — Complications caused by fluctuations in prosperity of groups studied, 414. — Advantages of discussing problem in terms of functions, 417. — Cohesion of functions, 417. — The problem of rating the functions, 419. — Accessibility and the costs of friction, 420. — Layout determined by the minimizing of the costs of friction; an hypothesis, 422, — The hypothesis explained and tested, 423. — Distorting and retarding factors, 429. — Primary and ancillary activities, 430. — The economic basis of zoning, 431.